The social background of elite executives: The Swedish case - Magnus Henrekson; Odd Lyssarides (Research Institute of Industrial Economics (IFN), 2016)
Sweden is often described as a country where intergenerational social mobility is high, but research also shows that social mobility decreases the closer one gets to the extreme top of the income distribution. We study the occupational mobility for an extreme elite group in society: the CEOs of Sweden's 30 largest public firms since 1945. To our knowledge, there exists no similar study for any other country. The study is based on a hand-collected data set consisting of 229 former and current CEOs who grew up in Sweden and born between the late1800s and 1970. We have information about paternal occupations for 185 (81 percent) of them, and 60 percent grew up in Social Group I, which implies an overrepresentation for Social Group I by a factor of 9.7. Consequently, Social Groups II and III are underrepresented. However, almost four out of ten CEOs born in the 1940s came from Social Group III and toward the end of the period, the share coming from Social Group II roughly doubled to about 35 percent. Wallenberg-controlled firms were slightly more likely to have CEOs with a Social Group III background. More than half of the CEOs have a father holding a managerial position. Seven of the CEOs have noble surnames, which implies an overrepresentation equal to that of Social Group I; however, among CEOs born after 1939 only two come from a noble family, which suggests a drop in the advantage conferred by a noble background. Finally, less than five percent of the CEOs were members of a family that was a controlling owner or had a father who was also a large-firm CEO.
Keywords: J00; J62; Z13; 330; Social mobility; Chief executive officers; Occupational mobility; Sweden